2022
DOI: 10.1515/jbcpp-2021-0374
|View full text |Cite
|
Sign up to set email alerts
|

The effects of G protein-coupled receptor 30 (GPR30) on cardiac glucose metabolism in diabetic ovariectomized female rats

Abstract: Background Diabetic cardiometabolic disorders are characterized by significant changes in cardiac metabolism and are increased in postmenopausal women, which emphasize the role of 17β-estradiol (E2). Despite this, there are few safe and effective pharmacological treatments for these disorders. The role of G protein-coupled estrogen receptor (GPR30), which mediates the non-genomic effects of E2, is mostly unexplored. Methods I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The protective cardio-metabolic effects of GPER in diabetic patients ( 17 ) and menopausal-diabetic rats ( 15 ) have recently been reported, but the mechanisms involved are not yet well understood. Since both diabetes and menopause are associated with changes in cardiac metabolism, which lead to functional changes in the heart and reduced cardiac function ( 16 , 20 ), in this study, we used a model of postmenopausal diabetes to determine the impact of selective GPER agonist on cardiac lipid metabolism as a possible protective mediator. The most important findings of this study are as follows: First, T2DM increased the accumulation of lipids within cardiomyocytes by increasing the cardiac level of FFAs and the expression of CD36, as well as decreasing the expression of PPARα.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protective cardio-metabolic effects of GPER in diabetic patients ( 17 ) and menopausal-diabetic rats ( 15 ) have recently been reported, but the mechanisms involved are not yet well understood. Since both diabetes and menopause are associated with changes in cardiac metabolism, which lead to functional changes in the heart and reduced cardiac function ( 16 , 20 ), in this study, we used a model of postmenopausal diabetes to determine the impact of selective GPER agonist on cardiac lipid metabolism as a possible protective mediator. The most important findings of this study are as follows: First, T2DM increased the accumulation of lipids within cardiomyocytes by increasing the cardiac level of FFAs and the expression of CD36, as well as decreasing the expression of PPARα.…”
Section: Discussionmentioning
confidence: 99%
“…After 72 hours, blood samples were collected from their tails, and rats with a fasting blood sugar (FBS) of ≥ 300 mg/dL were considered diabetic and included in the study. After confirmation of T2DM, a vehicle (0.1% dimethyl sulfoxide [DMSO]; Sigma USA) and G1 (200 μg/Kg; Tocris Bioscience, USA) were administered intraperitoneally 3 days per week for 6 weeks ( 16 ). Body weight was recorded at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that there is a direct link between the consumption of HFD and aging (12), which is associated with tissue and systemic inflammation and general dysfunction of the body (13). On the other hand, the prevalence of inflammatory diseases in women is lower than in men, which is probably due to the effects of ovarian hormones, especially E2 (14,15). However, this protection decreases with age, menopause, and ovariectomy (16).…”
Section: Introductionmentioning
confidence: 99%
“…Es are undeniably protective in women, and their decline during and after menopause coincides with increased CV risk and HF development [ 11 ]. Es are known to positively impact cardiac function, remodeling, and metabolism among their functions [ 8 , 12 , 13 , 14 ]. For these reasons, E replacement therapy (ERT) has been proposed as a therapeutic strategy to treat post-menopausal women [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%